Microinclusive teaching in family science courses. Issue 5 (21st November 2022) - Fitzpatrick, Jacki
Abstract: The purpose of this article is to provide a summary of microaggressive (MA) and microinclusive (MI) issues in college teaching. In MA communications, individuals/groups are treated as invisible or comparatively less desirable. MA can have a detrimental impact on its targets (to whom comments or behaviors are directed) as well as bystanders who witness the aggression. As part of ethics in family scholarship, it is worthwhile for faculty to consider MA and learn about more prosocial/supportive options, such as MI. This article provides a brief overview of MA, MI teaching, ethical approaches to MA/MI guidance, and MI teaching examples in one family science course. These issues are also relevant to coursework in other HDFS department programs or tracks (e.g., developmental, policy and practice, therapy, community education).